Relationship Between Self-Esteem with the Ability of Emotional Managementi Victims of Bullying Teenager - Lepir, Yuliana Niwa; Trishinta, Sirli Mardianna; Rosdiana, Yanti (Universitas Airlangga, 2021)
Introduction: Victims of bullying teenager gets pressure that can lead to decrease selfesteem and emotional management skills. The aimed of this study is to know the relationship between self-esteem with the ability of emotional management in victims of bullying teenager at Sunan Giri junior high school Malang. Method: The research design used a correlational descriptive design with a cross sectional approach. The research population was 155 students in junior high school Sunan Giri Malang and 112 students was obtained by with simple Random Sampling. The independent variable in this study was self-esteem and dependent variable in this study was the ability to manage emotions. The data were collected by Rosenberg Self Esteem Scale and Emotion Regulation Questionnaire (ERQ) self-esteem Questionnaires and then analyzed by the Fisher's Exact test. Results: The results showed 69 (61.6%) respondents have low self-esteem and 65 (58.0%) respondents have negative category emotion management skills in victims of bullying teenajer. The results of the Fisher's Exact test showed there was a relationship between self esteem and the ability of emotional management in victims of bullying teenager in junior high school Sunan giri Malang (p = 0.000). Conclusions: There is a relationship between with self-esteem the ability of emotional management in victims of bullying teenager in Sunan giri junior high school Malang. For further research expected to examine other factors that cause self-esteem and emotional management skills such as physical conditions, parenting patterns and social classes.